Utilidad de la guía de Tokio 2018 para el diagnóstico y tratamiento de colecistitis aguda en el servicio de cirugía general del Hospital Iquitos “César Garayar García”, 2020 - Soto Reyes, Jorge German (2024)
Acute cholecystitis is a clinical and surgical condition that is distinguished by acute inflammation of the Gallbladder. This manifests clinically with discomfort in the abdomen with defense in the right hypochondrium, sometimes with fever; whose diagnosis consists of the evaluation of the patient, results of auxiliary examinations and ultrasound studies; The definitive treatment being surgical, whether by conventional or laparoscopic surgery. In Peru, not many studies have been carried out on the prevalence of Acute Cholecystitis, however, in studies carried out in certain populations, a prevalence that ranges between 10% to 14.3% was found. The main purpose of this research is to determine the usefulness of the 2018 Tokyo Guide, for the diagnosis and treatment of Acute Cholecystitis in the General Surgery Service of the Iquitos “Cesar Garayar García” Hospital, during the year 2020, in patients with clinical suspicion of Acute cholecystitis. The type of research to be carried out will be observational, multivariate and retrospective. The SPSS program in version 22 will be used for statistical analysis, with which the distribution will be determined through graphs; finding the specificity and sensitivity of the guide, at the same time carrying out the cross-relation of data tables with the same software.